The Effect of Resistance Bands on Underhand Passing Accuracy in Extracurricular Volleyball Players Aged 15-18 Years - Mar'atul Afifah; Trisnar Adi Prabowo; Asyidika Vito Indarto; Zakwan Yumna Dhuha Pahlavi; Ellysia Nura Permata (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2026)
This study was to analyze the effect of resistance band use on underhand passing accuracy in volleyball players aged 15-18 years in extracurricular activities. This study was a quasi-experimental study using a pretest–posttest with a control group design. The sample consisted of 14 students (8 males and 6 females) in each of the intervention and control groups. The resistance band training method was carried out for 6 weeks, covering arm muscle strengthening, shoulder stability, underhand passing coordination with elastic loads. The training intensity was arranged progressively from 60%-80%. Data collection used a modified Brady Volleyball Test. The results of this study, the Wilcoxon test showed that the intervention group had an effect on improving underhand passing accuracy (male: sig. 0.011 and female: sig. 0.026). Meanwhile, the control group had no effect. Mann-Whitney test showed a posttest difference between the intervention and control groups, with a sig. 0.001 for male students and a sig. 0.004 for female students. This conclusion suggests that the intervention group experienced increased accuracy in underhand passing after being given a training program using resistance bands. Future research could involve a larger sample size, a longer intervention duration, and addition of supporting variables.